2007
DOI: 10.1111/j.1572-0241.2007.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Capsule Endoscopy for Pediatric Small-Bowel Diseases

Abstract: Our experience, which includes the largest number of pediatric patients and the youngest child reported in literature, confirms that CE is a very useful system for the clinical work in suspected small-bowel diseases in infancy. The high rate of positive examination is due to the very careful selection of the patients, obligatory to conduct a safe examination since CE is not highly tested in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 27 publications
2
52
0
2
Order By: Relevance
“…Studies of adult patients have revealed that CE is superior to the small bowel series for evaluating the small intestine [1][2][3]. A number of recent studies on pediatric patients have demonstrated that CE is also a useful in children with abdominal complaints, although the application of CE in this patient population has received relatively less attention compared to the adult patient population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The indications for CE in both children and adults include obscure gastrointestinal bleeding (OGIB), Crohn's disease (CD), and lymphangiectasia; in adults, suspected tumors of the small bowel also suggest the need for CE [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…Studies of adult patients have revealed that CE is superior to the small bowel series for evaluating the small intestine [1][2][3]. A number of recent studies on pediatric patients have demonstrated that CE is also a useful in children with abdominal complaints, although the application of CE in this patient population has received relatively less attention compared to the adult patient population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The indications for CE in both children and adults include obscure gastrointestinal bleeding (OGIB), Crohn's disease (CD), and lymphangiectasia; in adults, suspected tumors of the small bowel also suggest the need for CE [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…In a recent paediatric series [108], cap- sule retention occurred in 1/28 known cases of IBD. In the paediatric literature there are reports of only three cases of capsule retention in strictured small bowel that did not respond to corticosteroids and required surgical intervention [108,111,115]. Use of a patency capsule can decrease the risk of capsule retention and has been used in paediatric patients with good effect [64].…”
Section: Sbce: Safety and Prior Investigationsmentioning
confidence: 99%
“…21 However, CE has been used safely in much younger children and the FDA cleared its use for children older than 2 years of age in 2009. 4,22 Advantages in young children include the ability to image the small bowel without radiation exposure for CT scans or small bowel enterography, or a requirement for general anesthesia in order to undergo enteroscopy. 23 In the largest pediatric study to date, 87 patients ages 18 months to 18 years underwent successful CE without any reported complications.…”
Section: What Is the Youngest Age Patient That Can Safely Tolerate Ce?mentioning
confidence: 99%
“…23 In the largest pediatric study to date, 87 patients ages 18 months to 18 years underwent successful CE without any reported complications. 4 It should be noted that young children required ''training'' prior to CE by learning to swallow hard candies with the approximate size as the capsule. Endoscopic placement under general anesthesia into the stomach or duodenum was required in 7 patients (ages <6 Â 4, 9 years, 10 years, 11 years) either because of very young age or inability to swallow the capsule.…”
Section: What Is the Youngest Age Patient That Can Safely Tolerate Ce?mentioning
confidence: 99%
See 1 more Smart Citation